The Governance of Water Use in Northwest Mexico: A Qualitative and Quantitative Based Study - Santes-Alvarez, Ricardo V. (European Scientific Journal, ESJ, 2017)
In Mexico, the working of government institutions lags far behind the aims of good governance and sustainable development. Institutions deviate from those goals when they circumvent their duties to general wellbeing to favour powerful interest groups. The issue is even more of a concern in lands of high economic value, where the competition for water is strong. San Quintin Region, in the arid northwest part of the country, is symbolic; it is a rich agro-productive area inserted in the international market from way back, yet its economic success contrasts with worries regarding social conflict and environmental decline due to water misuse. Allegedly, if current exploitation trends remain unchanged, the viability of the ecosystem as a whole will be at risk soon. In this article, it is argued that the administration and management of water runs up against the aims of sustainable development; hence, measures to improve governance are needed. The main objective was to investigate the institutional and social context in which the problem occurs, so as to unveil the prospects of improvement. A qualitative and quantitative methodology suggested that in San Quintin, governance of water use reflects dubious institutional workings. It is unjust, because it fosters an inequitable treatment of the local population; also, it is environmentally damaging in view of the overexploitation of extant resources, often to the point of depletion. Furthermore, water use lacks context-focus, due to the centralised decisionmaking process. All in all, governance might progress through decisive reforms to social and institutional practices.